As noções de educação e disciplina em pais que agridem seus filhos - Vasconcelos, Alexsandra Cassol de; Souza, Marjane Bernardy (Psico, 2006)
O presente trabalho investigou as noções de educação e disciplina em pais que agrediram seus filhos e osrecursos educativos por eles utilizados. Participaram do estudo cinco mães que haviam apresentado algumepisódio de abuso físico contra seus filhos. As informações obtidas foram examinadas através de uma análisede conteúdo qualitativa que gerou seis categorias temáticas. Os achados da pesquisa sugerem que as mãesacreditavam no valor da obediência e da punição física como recursos educativos. Ainda, os dados obtidospermitiram notar que as participantes consideravam o diálogo e o afeto como técnicas educativas importantes,porém não conseguiram colocar em prática estas formas de educar. Palavras-chave: Violência doméstica; abuso físico; práticas educativas; relação pais-filhos. ABSTRACT The conception of education and discipline in parents who attack their childrenThe present work investigated the conception of education and disciplines in parents who had attacked theirchildren and the educative resources used for them. Five mothers had participated of the study who hadpresented some episode of physical abuse against their children. The information was examined through aqualitative analysis of the content, what generated six thematic categories. The research suggests that themothers believed in the value of the obedience and the physical punishment as educative resources. Yet, thedata allowed to observe that the participants considered the dialogue and the feeling as important educativepractices, however they hadn’t obtained to put into practice these forms to teach. Key words: Domestic violence; physical abuse; educative practices; parents-children relations.